1,3,4-Oxadiazole N-Mannich Bases: Synthesis, Antimicrobial, and Anti-Proliferative Activities - Lamya H. Al-Wahaibi; Ahmed A. B. Mohamed; Samar S. Tawfik; Hanan M. Hassan; Ali A. El-Emam (Molecules, 2021)
The reaction of 5-(3,4-dimethoxyphenyl)-1,3,4-oxadiazole-2(3H)-thione 3 with formaldehyde solution and primary aromatic amines or 1-substituted piperazines, in ethanol at room temperature yielded the corresponding N-Mannich bases 3-arylaminomethyl-5-(3,4-dimethoxyphenyl)-1,3,4-oxadiazole-2(3H)-thiones 4a–l or 3-[(4-substituted piperazin-1-yl)methyl]-5-(3,4-dimethoxyphenyl)-1,3,4-oxadiazole-2(3H)-thiones 5a–d, respectively. The in vitro inhibitory activity of compounds 4a–l and 5a–d was assessed against pathogenic Gram-positive, Gram-negative bacteria, and the yeast-like pathogenic fungus Candida albicans. The piperazinomethyl derivatives 5c and 5d displayed broad-spectrum antibacterial activities the minimal inhibitory concentration (MIC) 0.5–8 μg/mL) and compounds 4j, 4l, 5a, and 5b showed potent activity against the tested Gram-positive bacteria. In addition, the anti-proliferative activity of the compounds was evaluated against prostate cancer (PC3), human colorectal cancer (HCT-116), human hepatocellular carcinoma (HePG-2), human epithelioid carcinoma (HeLa), and human breast cancer (MCF7) cell lines. The optimum anti-proliferative activity was attained by compounds 4l, 5a, 5c, and 5d.